Performance Analysis of PT. Bina Wahyu Ramadhany's Website Using GTmetrix - Diana Rosilawati (Universitas Mercu Buana Yogyakarta, 2025)
Bina Wahyu Ramadhany is a company specializing in Occupational Safety and Health (K3) services. This study aims to evaluate the effectiveness and efficiency of the company's website as an information source for users. The analysis ensures that the website is accessible, delivers accurate and up-to-date information, and provides an optimal user experience. Website performance testing is conducted using GTmetrix, a tool that assesses website speed and efficiency while offering recommendations for potential improvements. Additionally, Speedtest.net is utilized to measure the stability and speed of internet access on the testing devices. The results from GTmetrix analysis indicate that the PT. Bina Wahyu Ramadhany website achieved an overall Grade A score with a 99% performance rating, marked by a green indicator. This rating signifies that the website's performance is classified as excellent. Based on these findings, it can be concluded that a higher performance score correlates with better website accessibility and an enhanced user experience.